Nonsymbolic and symbolic magnitude comparison skills as longitudinal predictors of mathematical achievement. (August 2017) - Xenidou-Dervou, Iro; Molenaar, Dylan; Ansari, Daniel; van der Schoot, Menno; van Lieshout, Ernest C.D.M.
Abstract: What developmental roles do nonsymbolic (e.g., dot arrays) and symbolic (i.e., Arabic numerals) magnitude comparison skills play in children's mathematics? We assessed a large sample in kindergarten, grade 1 and 2 on two well-known nonsymbolic and symbolic magnitude comparison measures. We also assessed children's initial IQ and developing Working Memory (WM) capacities. Results demonstrated that symbolic and nonsymbolic comparison had different developmental trajectories; the first underwent larger developmental improvements. Both skills were longitudinal predictors of children's future mathematical achievement above and beyond IQ and WM. Nonsymbolic comparison was moderately predictive only in kindergarten. Symbolic comparison, however, was a robust and consistent predictor of future mathematics across all three years. It was a stronger predictor compared to nonsymbolic, and its predictive power at the early stages was even comparable to that of IQ. Furthermore, the present results raise several methodological implications regarding the role of different types of magnitude comparison measures. Highlights: We assessed the development of nonsymbolic and symbolic magnitude comparison skills. And examined their unique predictive role for future mathematics beyond WM and IQ. Symbolic processing showed larger developmental growth rates than nonsymbolic. Nonsymbolic processing played a small unique predictive role only in kindergarten. Symbolic played a robust unique predictive role – akin to IQ – across the 3 years.